Amino acid sequence of porcine spleen cathepsin D. - Shewale, J G (1984)
The amino acid sequence of porcine spleen cathepsin D heavy chain has been determined and, hence, the complete structure of this enzyme is now known. The sequence of heavy chain was constructed by aligning the structures of peptides generated by cyanogen bromide, trypsin, and endo-proteinase Lys C cleavages. The structure of the light chain has been published previously. The cathepsin D molecule contains 339 amino acid residues in two polypeptide chains: a 97-residue light chain and a 242-residue heavy chain, with a combined Mr of 36,779 (without carbohydrate). There are two carbohydrate units linked to asparagine residues 70 and 192. The disulfide bond arrangement in cathepsin D is probably similar to that of pepsin, because the positions of six half-cystine residues are conserved. The active site aspartyl residues, corresponding to aspartic acid-32 and -215 of pepsin, are located at residues 33 and 224 in the cathepsin D molecule. The amino acid sequence around these aspartyl residues is strongly conserved. Cathepsin D shows a strong homology with other acid proteases. When the sequence of cathepsin D, renin, and pepsin are aligned, 32.7% of the residues are identical. The homology is observed throughout the length of the molecules, indicating that three-dimensional structures of all three molecules are similar.